2015
DOI: 10.1097/md.0000000000001994
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Effective Rate of Different Branches of Idiopathic Trigeminal Neuralgia After Single Radiofrequency Thermocoagulation

Abstract: To evaluate the efficacy of computed tomography (CT) guided single radiofrequency thermocoagualtion (RFT) in 1137 patients with idiopathic trigeminal neuralgia after a follow-up period of 11 years, specially focused on duration of pain relief in different branches of trigeminal nerve, side effect, and complications.Retrospective study of patients with idiopathic trigeminal neuralgia treated with a single CT guided RFT procedure between January 2002 and December 2013.The mean follow-up time was 46.14 ± 30.91 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 22 publications
2
39
2
Order By: Relevance
“…Among these cases, 15 (24.2%) patients had moderate facial numbness (BNI score III) and 2 (3.2%) had severe facial numbness (BNI score IV) that affected their quality of life. The severity of facial numbness at 75°C in our study is less than that reported by Tang et al, [6] who adopted RFT at 75°C to 85°C, and the incidence of facial numbness at 75°C is also lower than that in previous reports, including one report of RFT at a higher temperature in which 98% of patients had facial numbness [37] and a report by Lai et al [5] in which 87.8% of patients had facial numbness after RFT at 75°C for treatment of recurrent TN. There were 8 (12.9%) patients who had mild facial numbness after RFT at 68°C in the current study, and this rate is also lower than that previously reported for RFT at a higher temperature.…”
Section: Discussioncontrasting
confidence: 88%
See 4 more Smart Citations
“…Among these cases, 15 (24.2%) patients had moderate facial numbness (BNI score III) and 2 (3.2%) had severe facial numbness (BNI score IV) that affected their quality of life. The severity of facial numbness at 75°C in our study is less than that reported by Tang et al, [6] who adopted RFT at 75°C to 85°C, and the incidence of facial numbness at 75°C is also lower than that in previous reports, including one report of RFT at a higher temperature in which 98% of patients had facial numbness [37] and a report by Lai et al [5] in which 87.8% of patients had facial numbness after RFT at 75°C for treatment of recurrent TN. There were 8 (12.9%) patients who had mild facial numbness after RFT at 68°C in the current study, and this rate is also lower than that previously reported for RFT at a higher temperature.…”
Section: Discussioncontrasting
confidence: 88%
“…However, these studies have focused mainly on overall treatment results of RFT, whereas the effects of different temperatures have not been investigated. This study was designed to compare efficacy, safety, and patient satisfaction after RFT at 75°C (a clinically common temperature) [5,6,27] and 68°C (a lower temperature) in cases of bilateral ITN, with the final purpose of providing definite guidance for clinicians. In order to exclude the effects of individual subjectivity on pain evaluation, the study was performed in patients with bilateral ITN and RFT was performed bilaterally at different temperatures on each side.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations